The CTSC-RAB38 Fusion Transcript Is Associated With the Risk of Hemorrhage in Brain Arteriovenous Malformations. Issue 1 (29th October 2020) - Yan, Zihan; Fan, Guangming; Li, Hao; Jiao, Yuming; Fu, Weilun; Weng, Jiancong; Huo, Ran; Wang, Jie; Xu, Hongyuan; Wang, Shuo; Cao, Yong; Zhao, Jizong
Abstract: Brain arteriovenous malformations (bAVMs) are congenital anomalies of blood vessels that cause intracranial hemorrhage in children and young adults. Chromosomal rearrangements and fusion genes play an important role in tumor pathogenesis, though the role of fusion genes in bAVM pathophysiological processes is unclear. The aim of this study was to identify fusion transcripts in bAVMs and analyze their effects. To identify fusion transcripts associated with bAVM, RNA sequencing was performed on 73 samples, including 66 bAVM and 7 normal cerebrovascular samples, followed by STAR-Fusion analysis. Reverse transcription polymerase chain reaction and Sanger sequencing were applied to verify fusion transcripts. Functional pathway analysis was performed to identify potential effects of different fusion types. A total of 21 fusion transcripts were detected. Cathepsin C (CTSC)-Ras-Related Protein Rab-38 (RAB38) was the most common fusion and was detected in 10 of 66 (15%) bAVM samples. In CTSC-RAB38 fusion-positive samples, CTSC and RAB38 expression was significantly increased and activated immune/inflammatory signaling. Clinically, CTSC-RAB38 fusion bAVM cases had a higher hemorrhage rate than non- CTSC-RAB38 bAVM cases (p < 0.05). Our study identified recurrent CTSC-RAB38 fusion transcripts in bAVMs, which may be associated with bAVM hemorrhage by promoting immune/inflammatory signaling.